2005
DOI: 10.1001/archpedi.159.3.255
|View full text |Cite
|
Sign up to set email alerts
|

Immigration, Race/Ethnicity, and Social and Economic Factors as Predictors of Breastfeeding Initiation

Abstract: Immigration status was strongly associated with increased breastfeeding initiation in this cohort, implying that cultural factors are important in the decision to breastfeed. Immigrants of all races/ethnicities initiated breastfeeding more often than their US-born counterparts. In addition, US-born minority groups initiated breastfeeding at rates at least as high as their white counterparts, likely due in part to high levels of education and income as well as to access to a medical care system that explicitly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
100
6
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(122 citation statements)
references
References 27 publications
(24 reference statements)
14
100
6
2
Order By: Relevance
“…Keegan et al, 34 further noted that this pattern is consistent with the corresponding differences in breast cancer incidence rates in the state. Our results are consistent with published reports on breastfeeding, which show that women born outside the US are more likely to breastfeed than those who are born in the US [36][37][38][39][40][41] and that language acculturation also plays a role in whether women choose to breastfeed, particularly among MAs. Results of studies that considered SES variables in their models show that less-acculturated women are more likely to breastfeed than those who are more acculturated.…”
Section: Discussionsupporting
confidence: 92%
“…Keegan et al, 34 further noted that this pattern is consistent with the corresponding differences in breast cancer incidence rates in the state. Our results are consistent with published reports on breastfeeding, which show that women born outside the US are more likely to breastfeed than those who are born in the US [36][37][38][39][40][41] and that language acculturation also plays a role in whether women choose to breastfeed, particularly among MAs. Results of studies that considered SES variables in their models show that less-acculturated women are more likely to breastfeed than those who are more acculturated.…”
Section: Discussionsupporting
confidence: 92%
“…Studies have found that immigrant women who were born in Mexico are more likely to initiate breastfeeding in the hospital than their Mexican-American counterparts born in the U.S. (7)(8)(9)(10)(11)(12)(13). However, few studies have examined the effect of acculturation on duration of breastfeeding beyond the postpartum period.…”
Section: Introductionmentioning
confidence: 99%
“…39 In particular, a higher incidence of preterm births among AfricanAmericans and Hispanics as compared with Caucasians has been observed. 6,40 Potential reasons for such disparity are differing genetic factors, 41,42 socioeconomic status, 43,44 psychosocial stressors/risks, for example, racism, home and neighborhood violence, depression, pregnancy-related anxiety. 24,45,46 In view of the fact that socioeconomic and psychosocial stressors likely will be unchanged following a premature delivery, one may reasonably presume that maternal stress brought on by these factors will remain following a premature delivery and be further intensified by concerns over a preterm infant's health.…”
Section: Introductionmentioning
confidence: 99%